Growth Regulation in Amphibian Pathogenic Chytrid Fungi by the Quorum Sensing Metabolite Tryptophol - Verbrugghe, Elin; Adriaensen, Connie; Martel, An; Vanhaecke, Lynn; Pasmans, Frank (Frontiers in Microbiology, 2019)
Amphibians face many threats leading to declines and extinctions, but the chytrid fungal skin pathogens Batrachochytrium dendrobatidis (Bd) and Batrachochytrium salamandrivorans (Bsal) have been identified as the causative factors leading to one of the greatest disease-driven losses of amphibian biodiversity worldwide. Infection may lead to different clinical outcomes, and lethal infections are commonly associated with unrestricted, exponential fungal growth in the amphibian epidermis. Mechanisms underpinning Bd and Bsal growth in the amphibian host are poorly understood. Here, we describe a quorum sensing mechanism that allows cell-to-cell communication by Bd and Bsal in order to regulate fungal densities and infection strategies. Addition of chytrid culture supernatant to chytrid cultures resulted in a concentration-dependent growth reduction and using dialysis, small metabolites were shown to be the causative factor. U-HPLC-MS/MS and in vitro growth tests identified the aromatic alcohol tryptophol as a key metabolite in regulating fungal growth. We determined tryptophol kinetics in both Bd and Bsal and confirmed the autostimulatory mode of action of this quorum sensing metabolite. Finally, we linked expression of genes that might be involved in tryptophol production, with in vitro and in vivo chytrid growth. Our results show that Bd and Bsal fungi use tryptophol to act as multicellular entities in order to regulate their growth.